PSYCHODIAGNOSTICS OF PRESCHOOL CHILDREN WITH DEVELOPMENTAL DISORDERS (European Journal of Interdisciplinary Research and Development, 2025)
This article explores the psychodiagnostic assessment of preschool-aged children with developmental disorders. It highlights the importance of early identification of cognitive, emotional, and behavioral challenges in children and emphasizes the need for reliable diagnostic tools and techniques. The paper analyzes modern approaches in psychodiagnostics, including observation methods, standardized tests, and play-based assessment strategies adapted to children’s individual needs. Practical recommendations are offered for improving the diagnostic process and providing targeted support in preschool education settings.